The Implementation of Muhawarah Learning in Madrasah Tsanawiyah - Fauziyah, Restu Ayu; Nursyamsiah, Nunung; Nurmala, Mia (research, training and philanthropy institution Natural Aceh, 2023)
One of the methods used in learning Arabic that can improve maharah kalam is muhawarah; the muhawarah method is often used in several Islamic boarding schools in Indonesia. The facts found by researchers in the field are that in MTs Persis 31 Banjaran, muhawarah is a particular subject studied at school. This research aims to discover the process of muhawarah learning at MTs Persis 31 Banjaran. This study used descriptive qualitative research with data collection techniques: observation, interviews, and documentation. After the data was collected, data analysis was carried out using the technique proposed by Milles and Huberman, namely data reduction, data presentation, and drawing conclusions. The research result shows that the process of muhawarah lesson at MTs Persis 31 Banjaran contains four core activities of muhawarah learning, including (1) memorizing mufrodat, (2) analyzing mufrodat, (3) translating conversations, (4) carrying out simple conversations. The teacher's skills in achieving learning objectives are very influential, one of which is regarding the methods used in muhawarah learning. Methods appropriate to students' material, infrastructure, and conditions can make it easier for teachers to achieve learning objectives and increase student enthusiasm for learning.